2018
DOI: 10.1038/s41598-018-26313-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the griffithsin anti-HIV microbicide and placebo gels on the rectal mucosal proteome and microbiome in non-human primates

Abstract: Topical microbicides are being explored as an HIV prevention method for individuals who practice receptive anal intercourse. In vivo studies of these microbicides are critical to confirm safety. Here, we evaluated the impact of a rectal microbicide containing the antiviral lectin, Griffithsin (GRFT), on the rectal mucosal proteome and microbiome. Using a randomized, crossover placebo-controlled design, six rhesus macaques received applications of hydroxyethylcellulose (HEC)- or carbopol-formulated 0.1% GRFT ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…It proved 50-fold less cytotoxic than cyanovirin, and it did not increase the level of activation markers in CD4 + T lymphocytes. Scalable manufacture of cyanovirin 19 and griffithsin 20 and validation of the safety and antiviral efficacy of griffithsin in mice and rabbits as a topical microbicide has been reported by O'Keefe et al, 21,22 Takebe et al, 23 Kouokam et al, 24 Farr Zuend et al 25 and Girard et al 26 Interestingly, Castillo-Acosta et al 27 recently demonstrated that Pradimicin, a mannosespecific agent purified from Actinomyces madura, can cure mice suffering from acute sleeping sickness caused by trypanosomes. 16 It induces only minimal changes in secretion of inflammatory cytokines and chemokines by epithelial cells and human PBMCs, does not markedly upregulate T cell activation markers and gene expression, and has no measurable effect on cell viability.…”
Section: Introductionmentioning
confidence: 90%
“…It proved 50-fold less cytotoxic than cyanovirin, and it did not increase the level of activation markers in CD4 + T lymphocytes. Scalable manufacture of cyanovirin 19 and griffithsin 20 and validation of the safety and antiviral efficacy of griffithsin in mice and rabbits as a topical microbicide has been reported by O'Keefe et al, 21,22 Takebe et al, 23 Kouokam et al, 24 Farr Zuend et al 25 and Girard et al 26 Interestingly, Castillo-Acosta et al 27 recently demonstrated that Pradimicin, a mannosespecific agent purified from Actinomyces madura, can cure mice suffering from acute sleeping sickness caused by trypanosomes. 16 It induces only minimal changes in secretion of inflammatory cytokines and chemokines by epithelial cells and human PBMCs, does not markedly upregulate T cell activation markers and gene expression, and has no measurable effect on cell viability.…”
Section: Introductionmentioning
confidence: 90%
“…Lectins primarily show antiviral, antibacterial, and antifungal activities. Specially one type of lectin, griffithsin, showed important antiviral activity and is nowadays considered a promise antiviral agent, with great potential concerning the prevention of sexually transmitted infections [48], including HIV [64]. Other important peptides are renin inhibitor tridecapeptide [65] and dipeptide [66], which demonstrated hypotensive effect dipeptide.…”
Section: Other Bioactive Compounds From Marine Seaweedsmentioning
confidence: 99%
“…In summary, griffithsin 12 shows tremendous promise as a topical antiviral agent, with great potential concerning the prevention of sexually transmitted infections. The compound's repeatedly proven efficacy, along with the safety studies of O'Keefe et al [87] and Girard et al [89], appears to be leading up to a pre-clinical stage of testing, which should happen soon and eventually pave the way for future clinical trials.…”
Section: Griffithsinmentioning
confidence: 99%